2018
DOI: 10.1371/journal.pone.0192277
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of triclosan-resistant genes in major pathogenic microorganisms revealed by metagenome and genome-wide analysis

Abstract: The substantial use of triclosan (TCS) has been aimed to kill pathogenic bacteria, but TCS resistance seems to be prevalent in microbial species and limited knowledge exists about TCS resistance determinants in a majority of pathogenic bacteria. We aimed to evaluate the distribution of TCS resistance determinants in major pathogenic bacteria (N = 231) and to assess the enrichment of potentially pathogenic genera in TCS contaminated environments. A TCS-resistant gene (TRG) database was constructed and experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
(96 reference statements)
1
7
0
Order By: Relevance
“…Several resistance mechanisms are mediated through changes in efflux pump expression, and TCS-associated cross-resistance has been suggested to act via efflux pumps [23,30]. In order to assess both these observations, we investigated the expression levels of several efflux components.…”
Section: There Were Significant Differences In the Expression Of Resimentioning
confidence: 99%
“…Several resistance mechanisms are mediated through changes in efflux pump expression, and TCS-associated cross-resistance has been suggested to act via efflux pumps [23,30]. In order to assess both these observations, we investigated the expression levels of several efflux components.…”
Section: There Were Significant Differences In the Expression Of Resimentioning
confidence: 99%
“…Our functional work suggests that TCS R FabV homologs may be ubiquitous in Aeromonas spp. Intrinsic TCS R in the related γ-Proteobacteria Pseudomonas aeruginosa , is also due to FabV [10, 17]. Although Pseudomonadales were more prevalent than Aeromonadales in our WW samples, no TCS R determinants were predicted to have originated from Pseudomonadales.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, functional screening for TCS R in soil metagenomic libraries identified diverse ENR homologues [11]. Additional in silico metagenome and genome-wide analyses have also evaluated the distribution of TCS R in pathogenic bacteria derived from potentially triclosan-contaminated environments, and found that long-term and extensive triclosan contamination could lead to the selective emergence of TCS R pathogens [17]. Accurate in silico prediction of TCS R depends on current knowledge of TCS R mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Considering this biocide as a prototype for the understanding of other antimicrobial agents, it has also been reported that this substance has increased antimicrobial resistance in laboratory models [28,65,66]. In contrast, with real-life application, the results do not show an increase in antimicrobial resistance after the use of triclosan [20].…”
Section: Triclosanmentioning
confidence: 99%